INOVASI STRATEGI MENINGKATKAN MINAT SISWA DALAM PEMBELAJARAN MATEMATIKA KELAS 5 SDN SENTUL 1 - Samsudin; Encep Supriatna (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
One of the biggest issues at SDN Sentul 1 class 5 is facing a lack of interest among students in learning mathematics. Low conceptual understanding and student learning outcomes are impacted by this. Low interest in mathematics courses is frequently brought on by repetitive teaching strategies and a lack of learning diversity, claims Bukhari (2020). Finding innovative teaching techniques that might boost students' enthusiasm in learning mathematics is crucial. The purpose of this study is to find creative approaches that can boost students' interest. This study employs a descriptive qualitative methodology that includes documentation analysis, instructor interviews, and observation. The study's findings demonstrated that incorporating technology through interactive learning applications, using visually appealing content, and implementing educational game-based learning strategies can all boost student interest. According to Lestari and Wibowo (2019), interactive learning materials are highly successful at grabbing students' interest and increasing their engagement with the material. According to Nurhayati (2021), students might be encouraged to participate more actively by receiving awards and positive feedback on a regular basis. According to Suryani and Pratama (2020), strong teacher participation in developing innovative learning and parent-school collaboration is also crucial. It is anticipated that this invention will increase student motivation, improve their comprehension of mathematical ideas, and make studying more enjoyable.